Oxydia platyterata Guenée, Sabulodes glaucularia (Snellen) AND "CAMPANITA" METER, THREE NEW DEFOLIATORS OF FOREST IMPORTANCE IN COLOMBIA - MADRIGAL-C., ALEJANDRO; WIESNER-R., LILIANA; ARANGO-G., MARÍA ISABEL (Revista Colombiana de Entomología, 1985)
In this study, three new species of measuring worms from the forests of Colombia are reported. They are Oxydia platypterata Guenée, Sabulodes glaucularia (Snellen), and an up to now unidentified species, which was named "Campanita inchworm". The three species were found on Pinus patula, and the last two also on Cupressus lusitanica and Eucalyptus spp. A description of the insects and the duration of their life cycles is given.